2015
DOI: 10.1002/iid3.78
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis cases presenting to primary care paramedics in Quebec

Abstract: Data on anaphylaxis cases in pre‐hospital settings is limited. As part of the Cross Canada Anaphylaxis Registry (C‐CARE), we assessed anaphylaxis cases managed by paramedics in Outaouais, Quebec. A software program was developed to prospectively record demographic and clinical characteristics as well as management of cases meeting the definition of the anaphylaxis. Univariate and multivariate logistic regressions were compared to assess factors associated with severity of reactions and epinephrine use. Among 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There is still much room for improvement with respect to knowledge about epinephrine as the initial treatment of anaphylaxis, intramuscular administration, doses, and prescription of EAIs [7–12 ]. Studies that reviewed healthcare databases in Canada [13, 14 ] and The Netherlands [15 ] reported similar findings. Interdisciplinary communication and education on anaphylaxis are the most frequently proposed solutions.…”
Section: Introductionmentioning
confidence: 59%
“…There is still much room for improvement with respect to knowledge about epinephrine as the initial treatment of anaphylaxis, intramuscular administration, doses, and prescription of EAIs [7–12 ]. Studies that reviewed healthcare databases in Canada [13, 14 ] and The Netherlands [15 ] reported similar findings. Interdisciplinary communication and education on anaphylaxis are the most frequently proposed solutions.…”
Section: Introductionmentioning
confidence: 59%
“…Additionally, our SR identified 31 previously published symptom-severity scoring systems referred to food allergic reactions 1 , 4 , 15 , 19 , 20 , 22 , 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 [ Table 1 ]. Twenty-three were primary studies providing new symptom-severity scoring systems to assess food-induced allergic reactions 1 , 4 , 19 , 20 , 22 , 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 58 [ Table 1 , Table 2 ]. Of note, we were able to pool primary data eligible for our SR only from 11 of them.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, we were able to pool primary data eligible for our SR only from 11 of them. 4 , 19 , 20 , 22 , 24 , 26 , 27 , 29 , 30 , 31 , 32 The remaining 20 studies provided new symptom-severity scores but not eligible primary data for our SR since they: a) included allergic reactions triggered by a different 58 or any allergenic source (ie, not only food); 46 , 47 , 48 , 50 b) or were based on self-reported diagnosis of food allergy; 1 , 42 , 45 , 49 c) or included food allergy diagnosis only based on IgE-sensitization without history of ingestion of the suspected culprit food; 44 d) or referred to oral immunotherapy trials. 43 Eight out of the 31 that included symptom-severity scores were provided by secondary research papers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 In one study, these factors were reported by 73% of patients reporting symptoms (1 case series: • High specific IgE serum levels (3 analyses of clinical practice 30 33 40 ) large skin prick wheal size (1 analysis 30 ), history of anaphylactic reactions (2 analyses 53 54 ) and low tolerated dose of food allergen (1 analysis 32 ) were associated with a higher risk of adverse events in some studies. Other analyses did not find an association between safety outcomes and history of anaphylactic reaction, 94 low tolerated dose of food allergen 53 or skin prick wheal size. 53 ; some have started enrolment from age 29 61 or one.…”
Section: A6 Long-term Follow-up For Safety and Tolerabilitymentioning
confidence: 85%